Storytelling, educational resource for the development of oral expression in first-year students of the Kinesiology programme at the Arturo Prat University (Contextos: Estudios de Humanidades y Ciencias Sociales, 2018)
The current Health System in Chile emphasizes the promotion and prevention as an essential axis of health work, where the education of the community as a methodology of intervention by health teams is of the utmost importance. This forces health professionals to develop communication skills. This base makes it necessary to address this social responsibility in such a way that it is possible to develop and perfect the tools that health professionals possess, to turn them into true communicators.The present article expresses the results of an academic experience that was developed, during the first semester of the year 2017, in the Communicative Skill Workshop that the students of the first year of the kinesiology course of the Arturo Prat University study, where the use of the "Counting" as a didactic resource had a positive impact, according to the opinion of the students, for the development of oral expression in public.